Selected issues of the investment process implementation in historic buildings on the example of the Castle of the Dukes of Mazovia in Ciechanów - Sobczak, Antoni Krzysztof (Protection of Cultural Heritage, 2018)
The content of the publication resulted from the author’s experience gained during the first stage of the revitalization process of Mazovian Dukes Castle in Ciechanów. The publication recalls the background of the 14th century site and describes its later history. It presents the state of restoration works and the state of archeological research preceding the process of revitalization. It also depicts the course of the investor’s action and the procedure of implementation. The publication points to selected difficulties of organizational, technological, financial, legal/administrative, and conservation nature which arose during the implementation and its degree of complexity. Moreover, the publication undertakes to evaluate the status of the implementation process and indicates its results and the need for further continuation of the restoration works.